2015
DOI: 10.1063/1.4914450
|View full text |Cite
|
Sign up to set email alerts
|

Striped pattern selection by advective reaction-diffusion systems: Resilience of banded vegetation on slopes

Abstract: For water-limited arid ecosystems, where water distribution and infiltration play a vital role, various models have been set up to explain vegetation patterning. On sloped terrains, vegetation aligned in bands has been observed ubiquitously. In this paper, we consider the appearance, stability, and bifurcations of 2D striped or banded patterns in an arid ecosystem model. We numerically show that the resilience of the vegetation bands is larger on steeper slopes by computing the stability regions (Busse balloon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
124
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(145 citation statements)
references
References 59 publications
20
124
1
Order By: Relevance
“…For simplicity, in this article we restrict the model to one spatial dimension and focus on constantly sloped terrains, that is, s(x)s. Note that general behaviour observed in the 1D model typically corresponds well to the behaviour of 2D patterns (Siero et al, ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…For simplicity, in this article we restrict the model to one spatial dimension and focus on constantly sloped terrains, that is, s(x)s. Note that general behaviour observed in the 1D model typically corresponds well to the behaviour of 2D patterns (Siero et al, ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Nonetheless, using idealized set‐ups with steady rainfall, many authors have analysed the transient dynamics resulting from these inherently transient partial differential equation (PDE) models and drawn insights on different issues, such as the rates of transitions (Yizhaq et al, ), transitions of patterns on the basis of rainfall (Roitberg & Shoshany, ; Zelnik & Meron, ), response to gradual environmental change (Dagbovie & Sherratt, ; Siteur et al, ), succession dynamics (Pueyo et al, ), the pseudosteady migration of vegetation bands (Rietkerk et al, ; Sherratt & Lord, ), colonization of a slope (Sherratt, ), or the relevance of the transient history of patterns (Sherratt, ). This has further been studied using the concepts of pattern selection and wavelength selection (Dagbovie & Sherratt, ; Siero et al, ; Zelnik & Tzuk, ) used to describe the process under which a given pattern (with a particular characteristic wavelength) is established. Pattern (wavelength) selection has been shown to be history dependent (Dagbovie & Sherratt, ; Zelnik & Tzuk, ).…”
Section: Introductionmentioning
confidence: 99%
“…History dependence (alternatively, trajectory dependence) and the transient dynamics of these systems are the result of time‐dependent rainfall (Baudena, Boni, Ferraris, von Hardenberg, & Provenzale, ; Baudena et al, ; D'Odorico, Laio, & Ridolfi, ; Guttal & Jayaprakash, ; Kletter et al, ; Zhao & Wang, ) and many complex responses to spatial heterogeneities (McGrath, Paik, & Hinz, ; Siero et al, ; Siteur et al, ; Sun, Li, Yu, & Jin, ; Tietjen, ; van der Stelt et al, ; Yizhaq et al, ; Zhao & Wang, ). It has been shown that many of these factors can coerce patterns (Bastiaansen et al, ) and can strengthen or weaken the ecosystem (Kletter et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…We note that the consideration of the one-dimensional model might overestimate the stability [43]. As we consider small perturbations, we can ignore terms that are nonlinear in terms of n and w .…”
Section: Differential Flow-induced Instabilitymentioning
confidence: 99%